Appreciative Listening Using Songs for Enhancing Learners' Comprehensibility of English Expression - Purba, Sharon Maria Magdalena; Zaki, Leil Badrah (Universitas Pendidikan Mandalika, 2022)
This study explores the impact of the implementation of appreciative listening using English songs on the development of students' knowledge of various expressions in English. In collecting data, 23 students from various majors and different universities were involved as participants. In this qualitative study, they were interviewed about their experiences in discovering the various uses of expressions in English songs and how their knowledge developed as they tried to explore the meaning of the expressions. They testified that through this learning method, their knowledge of the various units in the language increased and they even promoted this way of learning for other learners. The results showed that the concept of appreciative listening using songs helps learners increase their knowledge of English expressions. The involvement of songs in English courses was also proven to give a positive impact on the learning atmosphere and it also promotes autonomous learning. The results obtained from this study are in line with what researchers have found in the past; this method should be implemented in English learning for the wider community.